2012
DOI: 10.1037/a0027838
|View full text |Cite
|
Sign up to set email alerts
|

Gendered motivational processes affecting high school mathematics participation, educational aspirations, and career plans: A comparison of samples from Australia, Canada, and the United States.

Abstract: In this international, longitudinal study, we explored gender differences in, and gendered relationships among, math-related motivations emphasized in the Eccles (Parsons) et al. (1983) expectancy-value framework, high school math participation, educational aspirations, and career plans. Participants were from Australia, Canada, and the United States (Ns = 358, 471, 418, respectively) in Grades 9/10 at Time 1 and Grades 11/12 at Time 2. The 3 samples came from suburban middle to upper-middle socioeconomic back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
256
3
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(294 citation statements)
references
References 73 publications
(114 reference statements)
21
256
3
14
Order By: Relevance
“…Brown et al, 2008) and do not have the benefit of longitudinal attitudinal data (c.f. Watt et al, 2012) but are interested in considering whether students' reported understandings of the value of mathematics are related to their choice patterns and whether the current policy goals have a chance of success. We have not presented advanced statistical analyses here, in particular multi-level models of how schools and teachers influence students' attitudes and choices, although there is good evidence from earlier studies that the school attended does have an important impact upon the likelihood of choosing A-level Mathematics (Matthews & Pepper, 2007;Noyes, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown et al, 2008) and do not have the benefit of longitudinal attitudinal data (c.f. Watt et al, 2012) but are interested in considering whether students' reported understandings of the value of mathematics are related to their choice patterns and whether the current policy goals have a chance of success. We have not presented advanced statistical analyses here, in particular multi-level models of how schools and teachers influence students' attitudes and choices, although there is good evidence from earlier studies that the school attended does have an important impact upon the likelihood of choosing A-level Mathematics (Matthews & Pepper, 2007;Noyes, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst both study groups were generally pleased with their GCSE outcomes, the group no longer studying the subject reported GCSE to be far less interesting and enjoyable. These associations are to be expected and the relationships between a range of factors such as motivation, achievement, classroom culture, course choice and gender have been discussed at length (Nagy et al, 2006;Wang, 2012;Watt et al, 2012). Table 1 0% 25% 50% 75% 100%…”
Section: Key Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identify gains as essential for academic achievement and choice behavior in the demanding STEM subjects [Chow et al 2012;Watt et al 2012]. Motivation to study, which describes students' reasons for pursuing CS, also influences graduates' behavior [Pirker et al 2014].…”
Section: Factors That Influence Students' Behaviormentioning
confidence: 99%
“…The relationship between motivational beliefs and performance for male and female students' is important in unlocking the gendered mechanisms that affect mathematics performance and participation (e.g., Simpkins and Davis-Kean 2005;Watt et al 2012;Nagy et al 2010). Social and cultural barriers have been known to influence gendered motivational belief and achievement.…”
Section: Gender and Educational Aspirationsmentioning
confidence: 99%